Effect of Mindfulness Training on Emotional Stability of Karate Kata Athletes - Karisma Ayu Wulandari; Komarudin Komarudin; Mochamad Yamin Saputra; Geraldi Novian; Siti Nursaba (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
In karate kata, athletes often struggle to stabilize emotions during competition, which negatively affects concentration, movement precision, and overall per-formance quality. Emotional stability is crucial because kata demands high levels of concentration, precision, and self-control. This study aimed to determine the effect of mindfulness training on the emotional stability of karate kata athletes. Using an experimental method with a one-group pretest-posttest design, 15 kara-te athletes from Cimahi City aged 8–12 years were selected as samples. The re-search instrument was an emotional stability questionnaire consisting of 24 items across three dimensions that had been tested for validity and reliability. Data were analyzed using descriptive statistics, normality tests, homogeneity tests, and paired sample t-tests. The results indicated that mindfulness training significantly improved emotional stability (p < 0.001), with scores increasing from 66% to 73%, representing a 7% improvement. This enhancement in emotional regulation supports better execution of kata movements under competitive pres-sure. These findings suggest that mindfulness training is an effective psychologi-cal strategy for enhancing emotional stability among young karate kata athletes. Therefore, its integration into regular training programs is recommended to sup-port optimal athletic performance.